1998
DOI: 10.1021/ma980573k
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Naphthalene Thermotropic Copolyesters:  Divalent Salts and Tensile Mechanical Properties

Abstract: Novel ionic naphthalene thermotropic polymers (NTPs), based on wholly aromatic copolyesters, were synthesized, and their tensile mechanical properties were investigated. These ionic NTPs, containing 1 mol % ionic groups with divalent metal counterions (Ba, Ca, Mg, and Zn), exhibited thermotropic liquid crystallinity. Among them, the Ca salt NTP maintained a high molecular weight and exhibited excellent thermal and mechanical properties. Systematic comparison was made among nonionic NTP, ionic NTP (Na salt), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 15 publications
(58 reference statements)
5
36
0
Order By: Relevance
“…Within the development of synthetic polymers, tensile properties of liquid crystalline polymers have been enhanced by increasing ionic bonding between polymer chains, instead of covalent cross-links. [26] It is known that collagen molecules with terminal peptides in vitro, can be precipitated from solution, with some degree of polymorphism depending upon conditions used. [27] This includes segment long spacing (SLS) collagen, where aggregated segments are equal to the molecular length but have asymmetric banding patterns and fibrous long spacing (FLS) collagen, where there is a symmetric banding pattern repeated at a distance greater than the typical 67 nm.…”
Section: Full Papermentioning
confidence: 99%
“…Within the development of synthetic polymers, tensile properties of liquid crystalline polymers have been enhanced by increasing ionic bonding between polymer chains, instead of covalent cross-links. [26] It is known that collagen molecules with terminal peptides in vitro, can be precipitated from solution, with some degree of polymorphism depending upon conditions used. [27] This includes segment long spacing (SLS) collagen, where aggregated segments are equal to the molecular length but have asymmetric banding patterns and fibrous long spacing (FLS) collagen, where there is a symmetric banding pattern repeated at a distance greater than the typical 67 nm.…”
Section: Full Papermentioning
confidence: 99%
“…However, like other LCPs, these polymers exhibit rather poor mechanical properties in the transverse direction in contrast to the longitudinal direction, due to weak intermolecular interactions [2,4]. We have been exploring a new approach by which ionic groups (and ionic bonds) are introduced into thermotropic LCP chains to achieve better transverse/ compressive properties in addition to better tensile properties [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [3,5,6], we synthesized and characterized novel ionic NTPs that are wholly aromatic polyesters having meta-linked sulfoisophthalate (SI) units. All these ionic NTPs had fiber-forming molecular weights and exhibited liquid crystallinity with nematic mesophase texture over a wide range of temperature, without showing a transition to an isotropic phase at least up to 380 8C.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some fibers made by these polymers compete with the best ceramic fibers and are far superior to metal fibers. 2 However, some problems have limited the application of MLCPs as high-performance polymers. A major shortcoming of MLCPs is the large anisotropy of their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Weiss 12,13 used interfacial polymerization methods for the preparation of LC polyester ionomers with flexible spacers. Hara and coworkers 14 incorporated an ionic monomer, sodium 5-sodiosulfoisophthalic acid, into an all-aromatic LC polyester. Zentel and coworkers 15 studied several families of MLCP ionomers and concluded that ionic association stabilized the LC phase.…”
Section: Introductionmentioning
confidence: 99%